Encoding and Interpreting Neolithic Sites: World Heritage Temples in Malta - Avellino-Stewart, Marie (The international journal of religious tourism and pilgrimage, 2020)
Understanding and interpreting landscapes entails the encoding of symbols and deciphering of codes left on the palimpsest. Interpreting the Neolithic and more significantly Neolithic temple sites, is challenging and rife with contested meanings. The overall landscape is used by adherents of the New Religious Movements, on faith-based visits, and as an extension, spiritual fulfilment is sought in the Neolithic temples of Malta. The same landscape is then part of both the inner and outer pilgrimage in the context of not only the modern designer religions, but also of the established religions. This paper presents a case study of the Neolithic temple sites located in the Maltese Islands, which are significantly located at the centre of the Mediterranean Sea. The paper suggests that although these are shared spaces they are also contested space as the interpretation of these sites are firmly biased.